Magia(K) em teoria e prática, de Aleister Crowley : tradução direta do original britânico, organização, introdução, estudo preliminar, edição e notas - Lima, Luana Camila de Souza (2017)
‗Magick in Theory and Practice‘ by Aleister Crowley: Direct translation of the original British, organization, introduction, preliminary study, edition and notes, consists of research and development, starting from a brief biographical note of the writers Fernando Pessoa and Aleister Crowley, culminating in the relation and analysis of their mystical writings and investigating the present occultism between the lines of their poems. In this way, it becomes possible to recognize the importance of both writers as far as literary studies are concerned, opening a range about the relationship between them, which began in an epistolary manner, with a later encounter in the Boca do Inferno (Mouth of Hell), an episode in which occurred the feigned suicide of Crowley, with the help of Pessoa. From these facts it is possible to prove the details in common between both, followed by the translation of Hymn to Pan into Portuguese language by Pessoa, a poem that appears in the epigraph of ‗Magick in Theory and Practice‘ and serves as a translation base as far as the Method of translation by Pessoa is concerned, based on existing methods and techniques of translation. The result of the research and development of the present work has a final product, the translation, edited and noted of ‗Magick in Theory and Practice‘ into Portuguese language, unpublished work titled: ‗Magia (k) in Theory and Practice.‘ Keywords: Fernando Pessoa, Aleister Crowley, translation, English language, occultism.